Covid-19 - What changed in the pediatric emergency room of a district hospital during the state of emergency? - Pessoa, Tânia (2021)
Introduction: The COVID-19 pandemic led to the adoption of a state of emergency in Portugal, during which hospital emergency admissions declined. The aim of this study was to analyze the differences in Pediatric Emergency Room admissions during the state of emergency compared to the pre-pandemic setting. Material and methods: Retrospective analytical observational study of patients admitted to the Pediatric Emergency Room of a group I hospital from March 19 to May 2 of 2020 and homologous 2019 period. Data regarding age, gender, admission origin and cause, recurrences, diagnosis, and discharge destination were collected. Results: During the state of emergency, a 78.7% reduction in Pediatric Emergency Room admissions occurred compared to the pre-pandemic state (956 in 2020 vs 4481 in 2019). The main differences between both periods were an increase in admission of patients with <1 year old; a decrease in admissions by own initiative together with an increase of external referrals; less infectious diseases diagnoses; a higher number of accidental intoxications or ingestions, foreign bodies, and burns; a decrease in recurrences; a relative increase of hospital transfers; and higher hospitalization rates despite their shorter duration. No increase was found in Observation Room admissions, referrals for hospital consultations, or deaths. Discussion: Most study findings may be due to a reduction in common reasons for attending the Pediatric Emergency Room, due to social distancing/quarantine and transport/circulation limitations imposed by the pandemic. Conclusions: There was no significant increase in patients’ disease severity and those with criteria for visiting the Pediatric Emergency Room continued to do so. Compliance with isolation measures and recommendations of the Directorate-General of Health (DGS) seem to have been met.